Analisis Pengembangan Desa Wisata sebagai Best Practice Penggunaan Dana Desa untuk Mewujudkan Good Governance dan Collaborative Governance - Rasmadi Didik Aryadi (Syntax Literate, 2023)
This study aims to analyze the development of tourism villages as a best practice in using village funds to realize good governance and collaborative governance. Tourism villages were chosen as case studies because of their potential to improve the economy of rural communities while maintaining the sustainability of the local environment and culture. The research method used is a qualitative approach with field studies, in-depth interviews, and document analysis related to the use of village funds in the development of tourism villages. Data collection is carried out through several stages, including identification of tourism village program implementation, community participation, village government involvement, and collaboration strategies with related parties. The results showed that the development of tourism villages has had a positive impact in the implementation of good governance and collaborative governance. The active participation of the community in planning and decision-making has increased accountability and transparency in the use of village funds. The village government acts as a facilitator and ensures the allocation of village funds in accordance with the priorities and needs of the community. Collaboration between village governments, government institutions, and related stakeholders is also the key to success in the development of tourism villages. Active involvement from all parties enables efficient use of resources and empowers rural communities in managing tourist destinations. This research suggests that tourism village development is the best model in using village funds to achieve good governance and collaborative governance at the village level. However, challenges such as sustainable resource management and community empowerment need to be addressed so that sustainability can be guaranteed